Solvent-induced construction of two zinc supramolecular isomers: synthesis, framework flexibility, sensing properties, and adsorption of dye molecules. Issue 58 (24th July 2017) - Song, Jiang-Feng; Luo, Jing-Jing; Jia, Ying-Ying; Xin, Li-Dong; Lin, Zhi-Zhu; Zhou, Rui-Sha
Abstract : Solvent-induced construction of two zinc supramolecular isomerism, sensing properties and adsorption of dye molecules. Abstract : Two zinc supramolecular isomers, formulated as α-[Zn( cis -cppca)(H2 O)] n (1 ) and β-[Zn( trans -cppca)(H2 O)] n (2 ), have been synthesized under solvothermal conditions and fully characterized (H2 cppca = 5-(3-carboxy-phenyl)-pyridine-2-carboxylic acid). Solvent-induced conformational isomerism of cppca 2− ligand and framework isomerism of1 and2 are both observed. Each distorted [Zn( cis -cppca)]2 unit joined four equivalent ones in an abnormal 2D puckered layer in compound1 ; however, compound2 displays a 3-D open framework with larger bi-edge channels constructed by 1D Zn–O–Zn chains and trans -cppca bridges, in which the internal edge is a nearly hexagonal channel with an approximate dimension of 14.51 Å and the external edge is a circular channel with an approximate dimension of 19.26 Å. Fluorescent properties indicated that compound1 displays an apparent fluorescence emission in acetone solvent; however, compound2 was very sensitive to acetone molecules which results in nearly 100% fluorescence quenching. Moreover, compounds1 and2 might be promising luminescent probes for the detection of Fe 3+ . The dye adsorption experiments demonstrated that compound2 showed good adsorption properties for MB and RhB molecules.